Age-specific performance of human papillomavirus E6/E7 mRNA assay versus cytology for primary cervical cancer screening and triage: community-based screening in China - Zhang, Jing; Liu, Guangcong; Yang, Di; Cui, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundIn the general population, primary human papillomavirus (HPV) testing is advocated for cervical cancer (CC) screening. HPV E6/E7 mRNA (Aptima HPV, AHPV) assays have garnered considerable traction due to their higher specificity when compared with HPV DNA assays. Here, we investigated age-specific primary AHPV screening assays and different triage strategies versus cytology to identify the best approach.MethodsBetween April 2018 and December 2021, we recruited female participants from 34 communities across Liaoning province and Qingdao City, China. Primary cervical screening protocols included liquid-based cytology (LBC) and AHPV assays, with females positive for any assays undergoing colposcopy. Genotyping (AHPV-GT) was conducted on all HPV-positive samples. Our primary outcomes were the identification of age-specific detection rates, colposcopy referral rates, and sensitivity and specificity values for high-grade squamous intraepithelial lesions or worse (HSIL+). AHPV and different triage strategy performances were also examined across different age cohorts.ResultsOur investigation included 9911 eligible females. Age-specific abnormal cytology rates were in the 6.1%–8.0% range, and were highest in 45–54-year olds. When compared with 35–44-or 45–54-year olds, HPV prevalence was highest in 55–64-year olds (12.2% or 11.6% vs.14.1%, P = 0.048 and P = 0.002, respectively). In 35–44-year olds, AHPV sensitivity for detecting HSIL+ was 96.6 (95% confidence interval [CI]: 89.7–100) - significantly higher than LBC sensitivity (65.5 [95% CI: 48.3–82.8], P < 0.001). When compared with LBC, HSIL+ detection rates by AHPV-GT using reflex LBC triage increased by 31.5% (9.6‰ vs. 7.3‰), and colposcopy referral rates decreased by 16.4% (5.1% vs. 6.1%). In 45–54-year olds, HSIL+ detection rates for AHPV-GT using reflex LBC triage were lower than LBC rates (6.2‰ vs. 6.6‰). In 55–64-year olds, AHPV sensitivity (97.2 [95% CI: 91.7–100.0]) was higher than LBC sensitivity (66.7 [95% CI: 50.0–80.6], P = 0.003). The area under the curve (AUC) value was not significantly different between AHPV-GT with reflex LBC triage and LBC (0.845 [95% CI: 0.771–0.920] vs. 0.812 [95% CI: 0.734–0.891], P = 0.236).ConclusionsPrimary AHPV screening using different triage strategies were different across different age cohorts. Thus, AHPV may be an appropriate primary screening method for 35–44 and 55–64 year old females, while AHPV-GT with reflex LBC triage may be more apt for 35–44 year old females.